Evidence for Feedback Regulation Following Cholesterol Lowering Therapy in a Prostate Cancer Xenograft Model. Issue 5 (30th November 2016) - Masko, Elizabeth M.; Alfaqih, Mahmoud A.; Solomon, Keith R.; Barry, William T.; Newgard, Christopher B.; Muehlbauer, Michael J.; Valilis, Nikolaos A.; Phillips, Tameika E.; Poulton, Susan H.; Freedland, Alexis R.; Sun, Stephanie; Dambal, Shweta K.; et al.
Abstract : BACKGROUND: Epidemiologic data suggest cholesterol‐lowering drugs may prevent the progression of prostate cancer, but not the incidence of the disease. However, the association of combination therapy in cholesterol reduction on prostate or any cancer is unclear. In this study, we compared the effects of the cholesterol lowering drugs simvastatin and ezetimibe alone or in combination on the growth of LAPC‐4 prostate cancer in vivo xenografts. METHODS: Proliferation assays were conducted by MTS solution and assessed by Student's t ‐test. 90 male nude mice were placed on a high‐cholesterol Western‐diet for 7 days then injected subcutaneously with 1 × 10 5 LAPC‐4 cells. Two weeks post‐injection, mice were randomized to control, 11 mg/kg/day simvastatin, 30 mg/kg ezetimibe, or the combination and sacrificed 42 days post‐randomization. We used a generalized linear model with the predictor variables of treatment, time, and treatment by time (i.e., interaction term) with tumor volume as the outcome variable. Total serum and tumor cholesterol were measured. Tumoral RNA was extracted and cDNA synthesized from 1 ug of total RNA for quantitative real‐time PCR. RESULTS: Simvastatin directly reduced in vitro prostate cell proliferation in a dose‐dependent, cell line‐specific manner, but ezetimibe had no effect. In vivo, low continuous dosing of ezetimibe, delivered by food, or simvastatin, delivered via an osmotic pump had no effect on tumor growth compared to control mice. In contrast, dual treatment of simvastatin and ezetimibe accelerated tumor growth. Ezetimibe significantly lowered serum cholesterol by 15%, while simvastatin had no effect. Ezetimibe treatment resulted in higher tumor cholesterol. A sixfold induction of low density lipoprotein receptor mRNA was observed in ezetimibe and the combination with simvastatin versus control tumors. CONCLUSIONS: Systemic cholesterol lowering by ezetimibe did not slow tumor growth, nor did the cholesterol independent effects of simvastatin and the combined treatment increased tumor growth. Despite lower serum cholesterol, tumors from ezetimibe treated mice had higher levels of cholesterol. This study suggests that induction of low density lipoprotein receptor is a possible mechanism of resistance that prostate tumors use to counteract the therapeutic effects of lowering serum cholesterol. Prostate 77:446–457, 2017 . © 2016 Wiley Periodicals, Inc.